Peripheral positioning of lysosomes supports melanoma aggressiveness - Katerina Jerabkova-Roda; Marina Peralta; Kuang-Jing Huang; Antoine Mousson; Clara Bourgeat Maudru; Louis Bochler; Ignacio Busnelli; Rabia Karali; Hélène Justiniano; Lucian-Mihai Lisii; Philippe Carl; Vincent Mittelheisser; et al. (Nature Communications)
Abstract Emerging evidence suggests that the function and position of organelles are pivotal for tumor cell dissemination. Among them, lysosomes stand out as they integrate metabolic sensing with gene regulation and secretion of proteases. Yet, how their function is linked to their position and how this controls metastasis remains elusive. Here, we analyze lysosome subcellular distribution in patient-derived melanoma cells and patient biopsies and show that lysosome spreading scales with melanoma aggressiveness. Peripheral lysosomes promote matrix degradation and cell invasion which is directly linked to the lysosomal and cell transcriptional programs. Using chemo-genetical control of lysosome positioning, we demonstrate that perinuclear clustering impairs lysosome secretion, matrix degradation and invasion. Impairing lysosome spreading significantly reduces invasive outgrowth in two in vivo models, mouse and zebrafish. Our study provides a direct demonstration that lysosome positioning controls cell invasion, illustrating the importance of organelle adaptation in carcinogenesis and suggesting its potential utility for diagnosis of metastatic melanoma.